2002
DOI: 10.1192/bjp.181.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the brain of a psychological treatment: Cognitive remediation therapy

Abstract: BackgroundThe results of one randomised control trial testing a psychological rehabilitation programme aimed at information processing strategies showed improvements in cognition post-treatment.AimsTo determine whether there are concomitant brain activation changes as a result of engaging in cognitive remediation therapy (CRT).MethodThree groups (patients receiving control therapyor CRT and a healthy control group) were investigated in a repeated measures design using the two-back test. Functional magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 28 publications
0
40
0
4
Order By: Relevance
“…Restorative models often gauge outcome by task-related neural activation of specific brain regions and normalization of task performance. In functional neuroimaging studies to determine whether there are concomitant brain activation changes as a result of engaging in restorative-based cognitive training, results demonstrated that normalized performance gains following memory training were correlated with increases in taskrelated activation of the frontocortical areas, particularly the left inferior frontal cortex (Wexler et al 2000;Wykes et al 2002). Normalized performance on memory tasks were associated with increased task-related activation of the same brain region that is activated during memory tasks in healthy individuals (Wexler et al 2000).…”
Section: Instructional Techniques and Cognitive Remediation Outcomesmentioning
confidence: 95%
“…Restorative models often gauge outcome by task-related neural activation of specific brain regions and normalization of task performance. In functional neuroimaging studies to determine whether there are concomitant brain activation changes as a result of engaging in restorative-based cognitive training, results demonstrated that normalized performance gains following memory training were correlated with increases in taskrelated activation of the frontocortical areas, particularly the left inferior frontal cortex (Wexler et al 2000;Wykes et al 2002). Normalized performance on memory tasks were associated with increased task-related activation of the same brain region that is activated during memory tasks in healthy individuals (Wexler et al 2000).…”
Section: Instructional Techniques and Cognitive Remediation Outcomesmentioning
confidence: 95%
“…In the last years neuroscientists have shown increasing interest in the rehabilitation of physical (e.g., Calautti and Baron, 2003;Nudo, 1999) and cognitive deficits (e.g., Carlomagno et al, 1997;Laatsch et al, 2004;Pizzamiglio et al, 2001;Robertson and Murre, 1999;Wykes et al, 2002) in brain-damaged patients. Neuropsychology is also interested in how rehabilitation may be influenced by findings from functional neuroimaging.…”
mentioning
confidence: 99%
“…Although the serum testosterone itself is likely not affected by group-therapy treatment per se, the relevance of this variable decreases with that therapy. There is a growing body of research demonstrating that physiological/biological events occur in response to psychotherapeutic treatment (e.g., Brody et al, 2001;Furmark et al, 2002;Goldapple et al, 2004;Wykes et al, 2002). The theoretical possibility does therefore exist, that serum testosterone levels themselves may be influenced by group therapy.…”
Section: Discussionmentioning
confidence: 97%